Xylooligosaccharide production by optimized sulfuric, acetic acid, and liquid hot water treatment of sugarcane leaves - Forsan, Carolina Froes [UNESP] (2022)
The content of xylan in sugarcane straw (culm top and leaves) is interesting to produce xylooligosaccharides (XOS), oligomers composed of xylose, which provide numerous health benefits. XOS were produced in this study by two types of treatment using sugarcane leaves: liquid hot water (LHW) and dilute acid (sulfuric and acetic acids), aiming to minimize sugar degradation production. A central composite design with axial points was performed to evaluate the effects of the independent variables on the hydrolysis production of XOS. Hydrolysis with acetic acid resulted in the conversion of xylan into XOS of 22.78% with 2% (%, m/v) of acid at 180 °C for 35 min. Hydrolysis with sulfuric acid resulted in XOS yield of 62.18% with 2% (%, m/v) of acid at 79.55 °C for 35 min. The LHW treatment using leaves resulted in XOS yield of 20.71% at 130 °C for 35 min. The LHW and dilute acid resulted in 0.018% and 0.195% (m/m) of furfural, respectively. For each ton of sugarcane leaves, an XOS production of 206.44 kg, 75.63 kg, and 68.69 kg can be estimated using sulfuric acid, acetic acid, and LHW, successively. The most effective treatment for XOS production was hydrolysis with dilute sulfuric acid; however, LHW generated lower degradation products.